THE EFFECT OF SOCIODRAMA METHOD ON JUNIOR HIGH SCHOOL STUDENTS’ SPEAKING SKILLS - I Gde Rama Putra Yuda; Zainul Aminin (Universitas Wiralodra, 2024)
This study investigates the effect of the sociodrama method on the speaking skills of junior high school students. Sociodrama, a form of role-playing that emphasizes social interactions and problem-solving, is hypothesized to enhance junior high school students' ability to articulate thoughts, engage in dialogues, and express emotions effectively. Researchers used pre-experimental research with one group pretest-posttest design. This design was developed to fulfill the research objectives, which include finding out the effect of using the Sociodrama Method on junior high school students' speaking skills. Before receiving sociodrama treatment, the average score of the experimental group was 58.65. Furthermore, after receiving treatment, the average score was 70.77. Thus, the average total pre-test and post-test scores increased by 12.129, caused by the implementation of the sociodrama method. It can be concluded that the implementation of the sociodrama method has a positive effect on students' speaking skills. The study concludes that incorporating sociodrama into the class can be a valuable strategy for developing students' speaking skills.